Functional networks of DIS3L2 in cancer and NMD - Garcia-Moreno, Juan (2019)
In the flow of information from DNA to mRNA to proteins, mRNAs undergo a number of processing steps, since they are synthesized in the nucleus, until they are translated in the cytoplasm. Eukaryotic cells tightly control the fidelity of this process, via quality control pathways, among them, the nonsense-mediated mRNA decay (NMD). NMD recognizes and degrades mRNAs harboring premature translation-termination codons (PTCs) and regulates normal and fully functional mRNA levels. A new branch of the NMD pathway is starting to be revealed, which is characterized by the involvement of the DIS3L2 3’ to 5’ exoribonuclease. This protein has special relevance, given its exosome-independent action and its uridylation-mediated decay. Interestingly, mutations on this ribonuclease induce deregulation of cell-cycle genes leading to a faster cell growth and decreased chromosome stability. In this project, we aim to analyze how DIS3L2 and uridylation regulate the human transcriptome, in order to shed light on how this ribonuclease is related to NMD and how its deregulation contributes to tumorigenesis. For this purpose, high-throughput mRNA sequencing has been performed in the SW480 colorectal cancer cell line depleted of DIS3L2 or DIS3L2 plus terminal uridylyl transferases (TUTases), TUT4 and TUT7. Gene ontology analysis over the set of genes up-regulated under those two conditions, show enrichment in molecular functions and biological processes related with cancer, and cell events directly implicated RNA processing and RNA degradation. Preliminary results on genetic features in the pool of deregulated transcripts also show significant differences between conditions, an important aspect that will guide us to determine grades of sensitivities in the decay of DIS3L2-subtrates. Currently, we are setting various approaches in order to unveil the role of DIS3L2 in oncogenesis and go deeper in its substrate preference.